2011
DOI: 10.1152/ajpheart.00503.2011
|View full text |Cite
|
Sign up to set email alerts
|

Human microvascular dysfunction and apoptotic injury induced by AL amyloidosis light chain proteins

Abstract: Light chain amyloidosis (AL) involves overproduction of amyloidogenic light chain proteins (LC) leading to heart failure, yet the mechanisms underlying tissue toxicity remain unknown. We hypothesized that LC induces endothelial dysfunction in non-AL human microvasculature and apoptotic injury in human coronary artery endothelial cells (HCAECs). Adipose arterioles (n = 34, 50 ± 3 yr) and atrial coronary arterioles (n = 19, 68 ± 2 yr) from non-AL subjects were cannulated. Adipose arteriole dilator responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 34 publications
9
80
0
1
Order By: Relevance
“…2 Recently, we showed that ex-vivo human leptomeningeal arterioles acutely exposed to soluble b-amyloid peptide 1-42 (Ab42), a major peptide implicated in AD, demonstrate endothelial dysfunction, and that this effect was similar in human abdominal subcutaneous adipose arterioles. 3 We showed similar induction of human arteriole endothelial dysfunction with exposure to light chain proteins derived from patients with AL amyloidosis, [4][5][6] suggesting common vascular toxicity among amyloidogenic proteins despite differences in amino acid composition. When nanoliposomes of less than 100 nM size composed of phospholipids phosphatidylcholine, cholesterol and phosphatidic acid (NLPA) were cotreated with amyloidogenic light chains, endothelial dysfunction was reversed and the b-sheet structure of the light chain protein was altered.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…2 Recently, we showed that ex-vivo human leptomeningeal arterioles acutely exposed to soluble b-amyloid peptide 1-42 (Ab42), a major peptide implicated in AD, demonstrate endothelial dysfunction, and that this effect was similar in human abdominal subcutaneous adipose arterioles. 3 We showed similar induction of human arteriole endothelial dysfunction with exposure to light chain proteins derived from patients with AL amyloidosis, [4][5][6] suggesting common vascular toxicity among amyloidogenic proteins despite differences in amino acid composition. When nanoliposomes of less than 100 nM size composed of phospholipids phosphatidylcholine, cholesterol and phosphatidic acid (NLPA) were cotreated with amyloidogenic light chains, endothelial dysfunction was reversed and the b-sheet structure of the light chain protein was altered.…”
Section: Introductionmentioning
confidence: 73%
“…The methods for arteriole preparation were previously published. 6 Arterioles ($80-250 mM diameter) were isolated from adipose tissue (living donors) or leptomeningeal tissue (cadaver donors), cannulated and pressurized until a final pressure of 60 mm Hg. Arteriole diameters were measured using videomicrometers.…”
Section: A42 Fibril Formationmentioning
confidence: 99%
“…Increased LV filling pressure, which causes increased wall stress due to diastolic dysfunction in cardiac amyloidosis, compresses myocardial capillaries, with subsequent decrease in their lumen. Endothelial function is impaired by microvascular toxicity induced by light chain in AL amyloidosis 27, 28. These mechanisms cause functional myocardial ischaemia, subclinical impairment of LV systolic function, and cardiac troponin release.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence indicates that toxic light chains may directly cause microvascular dysfunction, and the injury caused by light chains may induce apoptotic injury to ECs. 11,12 A more detailed functional study of the vascular function in patients with AL amyloidosis is required and, although some data have been published, 13 our group is further investigating the functional and clinical consequences of AL amyloidosis in the arterial vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Light chains may be directly toxic to the ECs and may thus alter vascular function. [9][10][11][12] There are limited data on endothelial function in patients with AL amyloidosis. 9,13 The study of the vascular function is complex, and surrogate markers of endothelial activation could be useful in understanding the potential role of endothelium in the development of symptoms and complications of AL amyloidosis.…”
Section: Introductionmentioning
confidence: 99%